MATLAB Symbolic Computation for the Steady State Modeling of Symmetrically Loaded Self Excited Induction Generator - Gurung, Krishna; Freere, P. (Kathmandu University Journal of Science, Engineering and Technology, 2007)
This paper presents the use of MATLAB symbolic computation technique to model and simulate self-excited induction generator. In this technique, the computer itself carries out both the tedious job of deriving the complex coefficients of the polynomial equations and solving them. Hence, the modeling and programming become very simple yet versatile. Good agreement between the results obtained from the conventional method and that obtained using symbolic computation validates the effectiveness of this new technique.